Extreme Programming-Based Fitness Center Application For Customer Progress Tracking And Exercise Schedule Management - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This study investigates the implementation of Extreme Programming (XP) in developing a Fitness Center application to track customer pro-gress and manage exercise schedules. The research includes system requirements analysis, architectural design, implementation of key fea-tures, and application testing and evaluation. The XP methodology facilitates iterative, collaborative, and adaptive development, resulting in an application responsive to customer needs. The research findings indicate that the application successfully records customer health pro-gress, flexibly manages exercise schedules, and provides reminder no-tifications. Testing and evaluation demonstrate that the application operates well, is integrated comprehensively, and performs satisfacto-rily regarding responsiveness, speed, and resource efficiency. User feedback also contributes positively to evaluating user satisfaction with the application. Thus, the use of XP in developing the Fitness Center application has provided an effective and efficient solution for achieving goals related to tracking customer progress and managing exercise schedules in the context of fitness and health